2002
DOI: 10.1038/416190a
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of receptor-interacting protein 2 in innate and adaptive immune responses

Abstract: Host defences to microorganisms rely on a coordinated interplay between the innate and adaptive responses of immunity. Infection with intracellular bacteria triggers an immediate innate response requiring macrophages, neutrophils and natural killer cells, whereas subsequent activation of an adaptive response through development of T-helper subtype 1 cells (TH1) proceeds during persistent infection. To understand the physiological role of receptor-interacting protein 2 (Rip2), also known as RICK and CARDIAK, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
335
4
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(364 citation statements)
references
References 22 publications
24
335
4
1
Order By: Relevance
“…Initial studies using RICK-deficient mice suggested that this kinase was involved in TLR signaling and that its absence conferred reduced cytokine responses after the stimulation of macrophages with preparations of LPS (9,10,14). In the current studies we have studied in detail the role of RICK in TLR signaling.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Initial studies using RICK-deficient mice suggested that this kinase was involved in TLR signaling and that its absence conferred reduced cytokine responses after the stimulation of macrophages with preparations of LPS (9,10,14). In the current studies we have studied in detail the role of RICK in TLR signaling.…”
Section: Discussionmentioning
confidence: 93%
“…However, the role of RICK in mediating Nod1 and Nod2 responses under more physiological conditions such as those induced by microbial stimuli in macrophages or in the animal remains to be investigated. In addition, RICK-deficient macrophages exhibited reduced responses when stimulated with lipoteichoic acid (LTA; TLR2 agonist), LPS (TLR4 agonist), and polyinosinic-polycitidylic acid (poly(I:C); a TLR3 agonist), but not CpG DNA (TLR9 agonist) (9,10,14). These studies suggested that RICK is involved in TLR signaling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…147,148 Early studies demonstrated that RIP2-deficient mice are viable but show impaired activation of NFkB in response to TLR signalling and are more resistant to LPSinduced lethal sepsis. 149,150 However, a more recent report, using synthetic and highly purified forms of TLR ligands, contend that TLR signalling is intact in cells from RIP2 null mice, but loss of RIP2 leads to abrogation of signalling in response to stimulation of nucleotide-binding oligomerization domain-containing protein 1 (NOD1) and NOD2 by their specific ligands or the intracellular pathogen Listeria monocytogenes. 151 These findings indicate that RIP2 mediates NOD1 and NOD2 signalling but not TLR signal transduction.…”
Section: Rip2 and Nod Signallingmentioning
confidence: 99%
“…4 demonstrate that TRIF is also required for the lipid-A-stimulated production of the intracellular proteins Pellino 1, RICK/Rip2, SOCS1, and SOCS3 that are considered to be involved in pattern recognition and cytokine receptor signaling. Whereas Pellino 1 appears to form an intermediate signaling complex with IRAK-1, IRAK-4, and TRAF6, leading to the activation of NF-‹ B [36], analysis of gene-deficient macrophages has shown that RICK/Rip2 is required for immune cell activation by Nod proteins and for optimal cytokine production in response to TLR2, TLR3, and TLR4 agonists [37,38]. SOCS1 and SOCS3 have been identified as critical negative regulators of IFN-+ and gp130 signaling, respectively [39].…”
Section: Trif Regulates the Expression Of Genes Encoding Immune Recepmentioning
confidence: 99%